2022
DOI: 10.1186/s13046-022-02429-8
|View full text |Cite
|
Sign up to set email alerts
|

SH3GLB1-related autophagy mediates mitochondrial metabolism to acquire resistance against temozolomide in glioblastoma

Abstract: Background The mechanism by which glioblastoma evades temozolomide (TMZ)-induced cytotoxicity is largely unknown. We hypothesized that mitochondria plays a role in this process. Methods RNA transcriptomes were obtained from tumor samples and online databases. Expression of different proteins was manipulated using RNA interference or gene amplification. Autophagic activity and mitochondrial metabolism was assessed in vitro using the respective cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Our previous studies showed that resistant CD133 + cells with SH3GLB1 deficiency could promote cell death after TMZ treatment [ 12 ]. However, the roles of SH3GLB1 on TICs or hierarchical cells are still unclear.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies showed that resistant CD133 + cells with SH3GLB1 deficiency could promote cell death after TMZ treatment [ 12 ]. However, the roles of SH3GLB1 on TICs or hierarchical cells are still unclear.…”
Section: Resultsmentioning
confidence: 99%
“…The human GBM cell lines, U87MG and A172, were purchased from the American Type Culture Collection (ATCC, VA, USA). Patient #5 cells were derived from a patient with GBM, as described in the previous studies [ 12 ]. They were cultured in a medium containing Dulbecco’s modified Eagle’s medium (DMEM) (Thermo Fisher Scientific, NMA, USA) with 10% fetal bovine serum (FBS) and 1–2% penicillin/streptomycin (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations